Macroinvertebrate-based multimetric predictive models for evaluating the human impact on biotic condition of Bolivian streams - Moya, Nabor (2011)
We developed and validated a single multimetric index based on predictive models that could evaluate anthropogenic disturbances in streams of three disparate ecoregions of Bolivia. To do so, we examined 45 candidate metrics reflecting different aspects of macroinvertebrate assemblage structure and function gleaned from available literature and for their potential to indicate degradation. More importantly, we integrated functional trait metrics to improve the sensitivity of our index. To quantify possible deviation from reference conditions, we first established and validated statistical models describing metric responses to natural environmental differences in the absence of any significant anthropogenic disturbance. We considered that the residual distributions of these models described the response range of each metric, independently of natural environmental influence. After testing the sensitivity of these residuals to a gradient of anthropogenic disturbance, we retained eight metrics that were used in the final assemblage index, four metrics based on richness and composition and four metrics based on biological traits. Our index performed well in discriminating between reference and disturbed sites, giving a significant negative linear response to a gradient of physical and chemical anthropogenic disturbances. After employing a probability survey design and sampling a relatively small number of sites throughout all major ecoregions of Bolivia, we believe our methodology can be used to develop a monitoring tool to evaluate status and trends in biological condition for streams of the entire country despite its complex and heterogeneous geology and climate.